Comparison of the Efficacy and Safety of Dexmedetomidine Administered in Two Different Modes Under Procedural Sedation and Analgesia in Plastic Surgery - Xia, Weipeng; Wang, Shanshan; Wei, Lingxin; Deng, Xiaoming; Yang, Dong; Sui, Jinghu; Liu, Juhui (Frontiers in Surgery, 2022)
Background: Dexmedetomidine (DEX), a highly selective α2-adrenergic receptor agonist, is now widely used in procedural sedation and analgesia. This study was designed to observe and compare the efficacy and safety of DEX administered in two different modes. Methods: In total, 100 patients were randomly divided into two groups to receive intravenous DEX 1 μg/kg over 15 min followed by 0.4-0.7 μg/kg/h infusion or DEX 1 μg/kg over 30 min followed by 0.4-0.7 μg/kg/h infusion. Heart rate (HR), mean arterial pressure (MAP), respiratory rate (RR), bispectral index (BIS), Ramsay Sedation Scores (RSS scores), the lowest respiratory rates (LRR), incidences of respiratory adverse events and frequencies of body movements were recorded. Recovery time, recall of intraoperative events, pain scores in PACU and satisfaction of patients and surgeons were assessed. Results: The BIS at time points from 5 min after anesthesia to the end of surgery in the intervention group were significantly higher (P<0.05). The RSS scores at time points from 5 min after anesthesia to immediately after induction with DEX were significantly higher in the intervention group (P<0.05). The HR at time points from the beginning of surgery to 30 min after local anesthesia, the MAP at time points from 30 min after local anesthesia to the end of surgery, and the RR at time points from 5 min after anesthesia to the end of surgery were significantly higher in the intervention group (P<0.05). Patients in the intervention group had higher LRR, lower incidences of respiratory adverse events, and shorter recovery time (P<0.05). Conclusions: Dexmedetomidine infused with a loading dose over 30 min had less impact on patients’ hemodynamics and respiration and could shorten the recovery time after anesthesia in procedural sedation and analgesia.